Investigation of fire protection performance and mechanical properties of thin-ply bio-epoxy composites - Cong, Xiaoye; Khalili, Pooria; Zhu, Chenkai; Li, Saihua; Li, Jingjing; Rudd, Chris; Liu, Xiaoling (2021)
Hybrid composites composed of bio-based thin-ply carbon fibre prepreg and flameretardant mats (E20MI) have been produced to investigate the effects of laminate design on their fire protection performance and mechanical properties. These flame-retardant mats rely primarily on expandable graphite, mineral wool and glass fibre to generate a thermal barrier that releases incombustible gasses and protects the underlying material. A flame retardant (FR) mat is incorporated into the carbon fibre bio-based polymeric laminate and the relationship between the fire protection properties and mechanical properties is investigated. Hybrid composite laminates containing FR mats either at the exterior surfaces or embedded 2-plies deep have been tested by the limited oxygen index (LOI), vertical burning test and cone calorimetry. The addition of the surface or embedded E20MI flame retardant mats resulted in an improvement from a base line of 33.1% to 47.5% and 45.8%, respectively. All laminates passed the vertical burning test standard of FAR 25.853. Cone calorimeter data revealed an increase in the time to ignition (TTI) for the hybrid composites containing the FR mat, while the peak of heat release rate (PHRR) and total heat release (TTR) were greatly reduced. Furthermore, the maximum average rate of heat emission (MARHE) values indicated that both composites with flame retardant mats had achieved the requirements of EN 45545-2. However, the tensile strengths of laminates with surface or embedded flame-retardant mats were reduced from 1215.94 MPa to 885.92 MPa and 975.48 MPa, respectively. Similarly, the bending strength was reduced from 836.41 MPa to 767.03 MPa and 811.36 MPa, respectively.